2013
DOI: 10.1626/pps.16.247
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Evaluation of Photoperiodic Sensitivity and Genetic Diversity in Common Buckwheat under a Controlled Environment

Abstract: Photoperiodic sensitivity is one of the most important factors determining whether a crop can adapt to and be cultivated under a broad range of conditions. In common buckwheat (Fagopyrum esculentum Moench), flowering time (flowering of the first flower) is a complex trait influenced by photoperiod, light quality, and temperature, which change daily under natural conditions, and their interaction. Common buckwheat shows a large genetic variation because of the outcrossing reproductive strategy of this species. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…For each of the 15 landraces, a total of 60 seeds (6 seeds × 2 rows × 5 planters) were sown in soil (Peat Pot V, NPK = 200:1000:200 mg/L; Hokkaido Peat Moss Co., Ltd., Hokkaido, Japan) in plastic planters (19 cm × 59 cm × 16 cm; height × length × width); for KSC2 and BNPL1, 36 seeds (6 seeds × 2 rows × 3 planters) were sown. On the basis of previous studies (Hagiwara et al 1998, Hara and Ohsawa 2013, Michiyama and Hayashi 1998, Michiyama et al 2005, Nagatomo 1961, Onda and Takeuchi 1942, the photoperiod was 15 h, which is a long-day condition that causes the expression of differences in photoperiod sensitivity among landraces. Fluorescent lamps for growing plants (Biolux-A FL40SBR-A; NEC Lighting, Ltd., Tokyo, Japan) were used to control the photoperiod.…”
Section: Evaluation Of Photoperiod Sensitivity and Preparation Of Segmentioning
confidence: 99%
“…For each of the 15 landraces, a total of 60 seeds (6 seeds × 2 rows × 5 planters) were sown in soil (Peat Pot V, NPK = 200:1000:200 mg/L; Hokkaido Peat Moss Co., Ltd., Hokkaido, Japan) in plastic planters (19 cm × 59 cm × 16 cm; height × length × width); for KSC2 and BNPL1, 36 seeds (6 seeds × 2 rows × 3 planters) were sown. On the basis of previous studies (Hagiwara et al 1998, Hara and Ohsawa 2013, Michiyama and Hayashi 1998, Michiyama et al 2005, Nagatomo 1961, Onda and Takeuchi 1942, the photoperiod was 15 h, which is a long-day condition that causes the expression of differences in photoperiod sensitivity among landraces. Fluorescent lamps for growing plants (Biolux-A FL40SBR-A; NEC Lighting, Ltd., Tokyo, Japan) were used to control the photoperiod.…”
Section: Evaluation Of Photoperiod Sensitivity and Preparation Of Segmentioning
confidence: 99%
“…Iwata et al (2005) showed that genetic diversity tends to be lower in populations with early flowering (summer ecotype), and the genetic structure differs between autumn and summer ecotype populations. Hara and Ohsawa (2013) accurately evaluated photoperiod sensitivity and genetic diversity under a controlled environment. Their results support the hypothesis that summer ecotypes were derived from autumn ecotypes by adaptation to the climate in northern Japan, i.e., adaptation from short-day to long-day cultivation, as outlined in Fig.…”
Section: Ecotype and Ecological Differentiationmentioning
confidence: 99%
“…Thus, autumn ecotype cultivars might be more tolerant to preharvest sprouting. The summer ecotype of buckwheat is considered to have derived from the autumn ecotype (Hara and Ohsawa 2013, Iwata et al 2005, Minami and Namai 1986. In double cropping, summer ecotype cultivars could show a greater yield than autumn ecotype cultivars, the yield of which is greatly reduced by long-day conditions Hayashi 1998, Yamazaki 1947).…”
Section: Preharvest Sproutingmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic variation in the timing of flowering and subsequent seed production is commonly observed in plants (e.g. Bourion et al, 2002;Franks et al, 2007;Hara and Ohsawa, 2013). Similarly, for facultative parthenogenetic animals which typically switch from asexual to sexual reproduction when environmental conditions deteriorate, there is genetic variation in the propensity to produce diapause propagules (P d ) in a given environment, suggesting that genotypes vary in their environmental cue thresholds (e.g.…”
Section: Introductionmentioning
confidence: 99%